THE EFFECT OF ENGLISH SUBTITLE IN “ZOOTOPIA” MOVIE IN SPEAKING SKILL - Fhuri Megawati; Ermawati Z. Nuroh (Universitas Pendidikan Mandalika, 2018)
This study investigated the effect of using English Subtitle in “Zootopia” Movie as media in speaking skill of SMPN 6 Sidoarjo. English Subtitle can describe as practice media to help the students when they understand to watch movie. The method used Quasi Experimental Design. The result of this study showed that the student could improve their ability in speaking skill through English subtitle. The data got from both pre-test and post-test score were analyzed using T-test formula. The result of calculation showed that in the significance degree of 5%, the value of t-test (to) is higher than t-table (tt) (19.90 > 1.99). According to the criteria of the test, the result showed that there is an effect of student’s in speaking skill using English subtitle. It can be concluded that English Subtitle in “Zootopia” movie as media is effective and applicable approach at the ninth grade of SMPN 6 Sidoarjo to improve student in speaking skill.